Anthropogenic petroleum signatures and biodegradation in subantarctic Macquarie Island soils. (June 2023) - Houlahan, Sarah B.; Errington, Ingrid; Hose, Grant C.; King, Catherine K.; George, Simon C.
Abstract: Special Antarctic Blend (SAB) diesel is the main fuel used on Macquarie Island and has been identified as the primary contaminant in several past spill events. This study evaluates the environmental impact of petroleum spills at high latitudes, in the soils of subantarctic Macquarie Island. Soil samples were collected from seven locations, including the "fuel farm" and main powerhouse that have been contaminated by petroleum in the past, and five reference locations, away from station infrastructure and from any obvious signs of contamination. Soils were solvent extracted and analysed using gas chromatography-mass spectrometry. The results show that both contaminated and uncontaminated sites contained a suite of different chain-length hydrocarbons. The more contaminated samples from the fuel farm and main powerhouse contained higher concentrations and a greater range of hydrocarbons that typically indicate numerous spills of varying ages. The hydrocarbon signature of samples collected near the fuel farm and at some of the main powerhouse sites was typical of SAB diesel. However, the hydrocarbon signature at other main powerhouse sites suggest contamination with a heavier fuel with different characteristics, including lower pristane/phytane ratios. Traces of C21 –C35 cyclic biomarkers in the spill sites may be derived from additional heavier fuels, and include a signature characteristic of crude oil derived from marine carbonate source rocks. Reference samples had lower concentrations of hydrocarbons, and these were dominated by high molecular weight n -alkanes with an odd-carbon-number predominance, typical of higher-plant derived lipids. Some reference samples also contained geochemical signatures that suggest that they too were contaminated by fuel oil. Variable levels of biodegradation of fuels in soils are consistent with a heterogenous site and a relatively slow rate of biodegradation. The occurrence of fresh spilled fuel overprinting biodegraded fuel from earlier spills is compelling evidence of multiple spills and complex mixing in the environment. Graphical abstract: Image 1 Highlights: Special Antarctic Blend diesel was sometimes spilled at subantarctic Macquarie Island. Soils analysed from contaminated areas at "fuel farm" (FF) and main powerhouse (MPH). Hydrocarbon signatures of FF and some MPH soils typical of SAB diesel. Some MPH sites contaminated with heavier fuel with different biomarker signature. Variable levels of biodegradation consistent with slow rate of biodegradation.